Market matters: interdependencies in the Indian media economy. (April 2020) - Parthasarathi, Vibodh; Athique, Adrian
In the complex operations of the Indian media economy, the phrase 'media markets' requires careful consideration as an analytical concept. As a noun, 'media markets' is typically used to refer to a spread of media businesses and/or consumer sectors. Closer examination reveals that there tend to be multiple markets operating simultaneously within any media business (for products, capital, labour, audience, etc.). This implies an 'economy of markets', transacting both across media formats and with markets situated outside of the media production process. Both 'media exchanges' and 'mediated exchanges' shape the dynamics of the inter-locking markets that constitute the Indian media economy. Thus, at the categorical level, we ask several questions: What are the boundaries of media markets? Who are the key actors? How are these transactional relationships valued? With these questions in mind, this article seeks to identify points of distinction in form and geography along with critical relationships between overlapping markets and underlying interests. We propose a topology of Indian media markets, organised via three levels, with treatment of each taking into consideration the synergistic character of media markets and how interdependency shapes functional norms, rules of exchange, and the embedding of media transactions.